Granulomatous gastritis induced by chronic peanut ingestion - Lee, Young Sub; Cho, Inju; Lee, Sung Hak; Jung, Eun Sun (Polish Journal of Pathology, 2023)
Granulomatous gastritis (GG) is a rare condition, with incidence between 0.08 and 0.35% in gastric biopsies. Various infectious and non-infectious aetiologies can be considered to cause granulomatous gastritis. Foreign bodies are a rare aetiology of GG and may result from foods, suture materials, or medications. We report a 59-year-old woman who had eaten large amounts of peanuts for more than 10 years and presented with epigastric discomfort. Esophagogastroduodenoscopy revealed multiple nodular lesions with ulcer scars at the stomach, which was diagnosed as GG probably caused by chronic peanut ingestion on endoscopic mucosal resection.